The Construction / Mazrul Azreen Aladin - Aladin, Mazrul Azreen (Faculty of Art and Design, 2021)
Fashion Design Construction is the foundation of fashion design which is a technical accomplishment that requires the knowledge, great skills and passion to turn a two-dimensional sketch into a successful and stunning final piece of garment that beautifully shapes and fits on a moving body. To prepare a well-finished garment, its stitching is done by combining the different garment components and involves both technical and design issues. Construction for Fashion Design guides designers through all the important processes which include techniques, theory and practical skills. All these processes lead to the essential and important stages of creating a garment. Starting from basic pattern block, pattern manipulation, fabric cutting, draping on the mannequin tosewing skills and ending by a variety of detailing finishing touches such as hand embroidery and machine embroidery. Construction offers a clear introduction and understanding to fundamental skills, knowledge and historical background or interest needed for successful garment construction. It is very important for designers to understand how a garment turns from two dimensional into three dimensional object. From sketches as starting process to pattern. Pattern drawing or pattern making is the process of creating a pattern by taking measurements from a person in order to create a foundation, which is a pattern used as the basis for the design to create a garment that suits the proportions of a human body. A pattern is a template from which the components of the garment are traced to fabric before being cut and assembled. The flat-pattern method is where the pattern is drawn on a flat surface of brown paper including all measurements, using rulers, curves and straight-edges. A pattern maker would also use various tools such as a tracing wheel and tailor chalk to mark the pattern. Usually, flat patterning begins with the creation of a block pattern that fits the wearer’s measurements.